2022
DOI: 10.1002/ecm.1548
|View full text |Cite
|
Sign up to set email alerts
|

Toward a “modern coexistence theory” for the discrete and spatial

Abstract: The usual theoretical condition for coexistence is that each species in a community can increase when it is rare (mutual invasibility). Traditional coexistence theory implicitly assumes that the invading species is common enough that we can ignore demographic stochasticity but rare enough that it does not compete with itself, even after it has reached a stationary spatial distribution. However, short‐distance dispersal of discrete individuals leads to locally dense population clusters, and existing theory brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Third, we found that the frequently used deterministic invasion criterion 1,5 did not yield useful predictions because it was satisfied for nearly all forests analysed here (equation 11) and failed to detect differences in the local extinction risk of species related to demographic stochasticity 14 . Additionally, it does not apply if rare species are more strongly aggregated than abundant species 9 , as observed here in temperate forests. This leads to conspecific population-level interaction coefficients that are not constant as commonly assumed 49 , but depend negatively on abundance (equation 7c).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Third, we found that the frequently used deterministic invasion criterion 1,5 did not yield useful predictions because it was satisfied for nearly all forests analysed here (equation 11) and failed to detect differences in the local extinction risk of species related to demographic stochasticity 14 . Additionally, it does not apply if rare species are more strongly aggregated than abundant species 9 , as observed here in temperate forests. This leads to conspecific population-level interaction coefficients that are not constant as commonly assumed 49 , but depend negatively on abundance (equation 7c).…”
Section: Discussionmentioning
confidence: 86%
“…The search for simple principles underlying the complex spatial structure and dynamics of plant communities is a long-standing challenge in ecology [1][2][3][4][5][6] . In particular, the relationship between the spatial distribution of plants and species coexistence is challenging to resolve in species-rich communities [7][8][9] . Analysing the spatial patterns of tree species in 21 large forest plots, we find that rare species tend to be more spatially aggregated than common species, and a latitudinal gradient in the strength of this negative correlations that increases from tropical to temperate forests.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of phenotypic plasticity in species coexistence or exclusion has attracted much attention in recent years (Berg & Ellers, 2010;Callaway et al, 2003;Miner et al, 2005;Turcotte & Levine, 2016), the major theoretical advancements with regard to species coexistence presume fixed traits on ecological time scales (Chesson, 2000;Ellner et al, 2022;Letten et al, 2017;Serván et al, 2018). In addition, the most illuminating studies on the interplay between phenotypic plasticity and coexistence are in plants, often focusing on plantspecific traits (reviewed in Hillerislambers et al (2012)).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological theory predicts that for N genotypes (different strains and species) to coexist in an ecosystem, they must be constrained by at least N independent limiting factors. These limiting factors can be resource types, interactions within and among species, and myriad environmental features [19][20][21][22][23][24][25] . When an ecosystem varies in space or time, the number of limiting factors can increase, and additional genotypes can coexist in the heterogeneous ecosystem, when otherwise they would be lost in a corresponding homogeneously mixed system 24,26 .…”
Section: Introductionmentioning
confidence: 99%